Adopting Proactive Environmental Strategy: The Influence of Stakeholders and Firm Size - Darnall, Nicole; Henriques, Irene; Sadorsky, Perry (Journal of Management Studies, 2010)
abstract While smaller firms are less likely to undertake as many environmental practices as larger firms, extant literature suggests that smaller firms may be more responsive to stakeholder pressures. This paper contributes to the development of stakeholder theory by deriving a size moderated stakeholder model and applying it to a firm's adoption of proactive environmental practices. The empirical results show that smaller firms are more responsive to value‐chain, internal, and regulatory stakeholder pressures. These findings suggest that researchers evaluating organizations and the natural environment should be cautious about associating stakeholder pressures directly with firms' environmental strategies. Rather, the relationship between stakeholder pressures and environmental strategy tends to vary with size.